2021
DOI: 10.3390/cancers13194926
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of EGFR-TKI Resistance in EGFR-Mutated Non-Small Cell Lung Cancer: Application to Biological Diagnostic and Monitoring

Abstract: Non-small cell lung cancer (NSCLC) is the most common cancer in the world. Activating epidermal growth factor receptor (EGFR) gene mutations are a positive predictive factor for EGFR tyrosine kinase inhibitors (TKIs). For common EGFR mutations (Del19, L858R), the standard first-line treatment is actually third-generation TKI, osimertinib. In the case of first-line treatment by first (erlotinib, gefitinib)- or second-generation (afatinib) TKIs, osimertinib is approved in second-line treatment for patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 232 publications
(500 reference statements)
2
35
1
Order By: Relevance
“…Another retrospective study confirmed the minor efficacy of first-generation EGFR TKIs in patients with G718X and L861Q [ 42 ]. Encouraging results come from the clinical activity of amivantamab, a bispecific antibody directed against EGFR and MET tyrosine kinase receptors, and against tumors with EGFR exon 20ins mutations [ 43 ]. However, we have to wait for the conclusion of ongoing phase III studies to better define its role in this patient setting.…”
Section: Egfr -Mutated Nsclcmentioning
confidence: 99%
“…Another retrospective study confirmed the minor efficacy of first-generation EGFR TKIs in patients with G718X and L861Q [ 42 ]. Encouraging results come from the clinical activity of amivantamab, a bispecific antibody directed against EGFR and MET tyrosine kinase receptors, and against tumors with EGFR exon 20ins mutations [ 43 ]. However, we have to wait for the conclusion of ongoing phase III studies to better define its role in this patient setting.…”
Section: Egfr -Mutated Nsclcmentioning
confidence: 99%
“…Off-target mechanisms of secondary resistance, occurring on different genes, are also possible [ 126 , 128 , 130 ]. So, in a similar manner to that described for many TKIs (notably those targeting EGFR mutations or ALK rearrangements), secondary resistance associated to KRAS G12C inhibitors can be linked to MET amplification [ 143 , 147 , 152 , 160 , 161 ]. A RET fusion can be a mechanism of secondary resistance since RET kinase domain activation leads to oncogenic signaling of the PI3K-AKT, JNKs, and BRAF–MEK–ERK pathways, thus promoting cell survival and tumor promotion [ 162 ].…”
Section: Resistance Mechanisms Induced In Non-small Cell Lung Carcino...mentioning
confidence: 98%
“…Some of the resistant mechanisms are certainly easier to assess with a tissue biopsy (such as a MET amplification) while other mechanisms may be identified using a liquid biopsy and/or a tissue biopsy (such as new KRAS mutations or BRAF mutations) [ 144 , 145 , 147 ]. Moreover, as different mechanisms of resistance occur at progression in patients treated with different TKIs, early detection of this mechanism can be done with blood samples by establishing monitoring, even before the radiological onset of tumor progression [ 160 , 161 ]. However, other mechanisms of resistance, notably histological transformation, can be assessed only with a tissue biopsy.…”
Section: Opportunities and Challenges For The Thoracic Pathologistsmentioning
confidence: 99%
“… A simplified scheme of signal transmission in cell and selected target points: EGFR, MEK, PGDFR, PI3K, RAF, and VEGFR for molecularly targeted drugs (protein kinase inhibitors) [ 14 , 15 , 16 , 17 , 18 ]. …”
Section: Figurementioning
confidence: 99%